Environmental education : a strategy for primary teacher education - Wagiet, Razeena (Rhodes University, Faculty of Education, Department of Education, 1997)
This research focuses on environmental education in initial teacher education, and is grounded in three interlinked and widely recognised assumptions. First, that education for sustainable living can assist in resolving some environmental problems that are contributing to the environmental crises of sustainability currently facing South Africa and the rest of the world. Second, that education for sustainable living can assist in the establishment of a new environmental ethic that will foster a sustainable way of living. Third, that teacher education is a vital process for the attainment of both. These assumptions inform the aim of this research, which is to explore the potential for the implementation of education for sustainable living, and to identify a strategy for this, for initial teacher education, for senior primary school student teachers in the Western Cape. The strategy is derived following the grounded theory approach, developed through the case study method. In the process of identifying the strategy, this study establishes that there are challenges at macro, meso and micro levels that are obstructing the changes necessary for education for sustainable living. Change theory provides the basis for explaining these shortcomings, by helping to identify the barriers that might obstruct the realisation of the changes that are necessary for education for sustainable living. These challenges need to be perceived in the light of overcoming three sets of barriers in the way of the potential implementation of education for sustainable living in teacher education. First are those that can be ascribed to the formal education system that, while clinging to Western, Eurocentric values on the one hand, bave also failed to secure a policy for environmental education on the other. Second are the barriers ascribed to the teacher educators themselves, with the whole notion of their powerlessness at its core. Finally, there are the logistical barriers, which encompass, for example, time and financial constraints. With these barriers as a backdrop, to facilitate the incorporation of environmental education into initial teacher education, the study identifies a need for the development of a strategy to secure that education for sustainable living assumes its rightful place in the curriculum for initial teacher education. This framework emerges from the theory grounded in the interviewees' responses during the research, and from the theory grounded in the literature. Central to this framework is for education for sustainable living to contribute to the realisation of real change, change that would further the transformation of our conflict-riddled and inequitable society towards a more democratic and just one. This thesis demonstrates that the realisation of the changes necessary for education for sustainable living demand a reconstruction of current teacher education in order to secure and to sustain an appropriate and sound education ethic to form the basis of a trans formative teacher education curriculum for sustainable living within initial teacher education. Except formal policy, but central to overcoming these barriers, is the need for professional development programmes for teacher educators. A strategy in this regard, is outlined.
Keywords: Environmental education -- Study and teaching (Elementary); Environmental education -- Study and teaching (Elementary) -- South Africa